PENGARUH ARUS KAS OPERASI, SIKLUS OPERASI, EFEKTIFITAS DEWAN KOMISARIS, DAN EFEKTIFITAS KOMITE AUDIT TERHADAP PERSISTENSI LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Mujiono, Mujiono; Hatta, Madani; Fachruzzaman, Fachruzzaman; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2021)
Purpose : This study aims to give empirical evidence on the operating cash flow, operasting cycle,  effectiveness of the board of commissioners and effectiveness of audit committee on earnings persistance. The sample used in the study was manufacture companies listed on the Indonesia Stock Exchange in 2014-2018 with a total sample of 400 observations.Research methodology : This study was tested using multiple regression analysis with the SPSS version 24 program. The sample used in this study was a manufacturing company listed on the Indonesia Stock Exchange in 2014-2018. The sample in this study was selected using the purposive sampling method with a total sample of 400 observations.Result : The results of the study indicate that operating cash flow and the effectiveness of the board of commissioners have a positive effect on earnings persistence, but for operating cycle variables and audit committee effectiveness have no effect on earnings persistence.Limitations : The limitation of this research is that some of the sample companies' financial and annual reports cannot be accessed, so that in terms of the number of samples, the number of samples is reduced and the results of the research may be less than optimal.Contribution : The implication of this research is to provide theoretical information about agency theory in which there is an agency conflict that can cause a decrease in earnings persistence so that monitoring costs are needed to minimize agency conflict. For manufacturing companies and for further research, this research is expected to provide additional information and understanding of what can encourage an increase in earnings persistence.